Princess in pink - Cabot, Meg. (New York : HarperCollins, 2004)
In a series of humorous diary entries, high school freshman (and Genovian Princess) Mia tries to get her reluctant boyfriend to take her to the prom.
1010
Accelerated Reader AR
Keywords: Proms -- Juvenile fiction; Princesses -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Diaries -- Juvenile fiction; Humorous stories; New York (N.Y.) -- Juvenile fiction